Analysis Of Arabic Language Sources on the History of the Local Rulers in the Struggle Against the Arab Caliphat Coination in the VII-VIII Centuries - Boymirzayev Ismoiljon Khasanovich (Zien Journals, 2024)
In the article, the Arab caliphate in the VII-VIII centuries to the invasion against in the struggle local of rulers to history about Arabic tongue sources analysis will be done
Keywords: Dinovari; Kitab al-akhbar at-tivol; Yakubi